The Influence of Coordination on Employee Work Effectiveness - Mustaki, Wawan; Abdussamad, Zuchri (International Journal of Economics and Business Management, 2025)
This study aims to determine the effect of coordination on the effectiveness of employee work at the Kabila District Office, Bone Bolango Regency. This research method uses a survey method with a quantitative research approach. Quantitative methods are directed at solving problems by presenting or describing the results of the study as they are. The data collection technique uses a questionnaire that will be tested for validity and reliability. The data analysis method in this study uses path analysis and the calculation operation uses the SPSS 20 program. The number of respondents in this study was 35 people. Based on the results of the study, it shows that coordination in the form of vertical coordination (X1) and horizontal coordination (X2) simultaneously affects the effectiveness of employee work (Y) at the Kabila District Office, Bone Bolango Regency, which is 0.742 (74.2%). Coordination activities apply to all work units, where each work unit carried out by various people can take place harmoniously and in balance in the desired direction, so a leader must be able to carry out a coordination action. Coordination in the form of vertical coordination (X1) partially influences the effectiveness of employee work (Y) at the Kabila Sub-district Office, Bone Bolango Regency, which is 0.501 or 50.1%. This means that vertical coordination in the form of giving work instructions to employees has been running well. Coordination in the form of horizontal coordination (X2) partially influences the effectiveness of employee work (Y) at the Kabila Sub-district Office, Bone Bolango Regency, which is 0.372 or 37.2%. This means that in coordinating unification actions or activities, direction given to activities at the same organizational level (apparatus) has not been carried out optimally.